Angiotensin-converting enzyme (ACE) inhibitor prescription affects non-small-cell lung cancer (NSCLC) patients response to PD-1/PD-L1 immune checkpoint blockers. (1st January 2020) - Medjebar, Soleine; Truntzer, Caroline; Perrichet, Anaïs; Limagne, Emeric; Fumet, Jean-David; Richard, Corentin; Elkrief, Arielle; Routy, Bertrand; Rébé, Cédric; Ghiringhelli, François
ABSTRACT: Angiotensin-converting enzyme (ACE) inhibitors are frequently used to treat hypertension and congestive heart failure. Preclinical data show that ACE plays a role on both innate and adaptive immune responses. Since interactions between ACE inhibitors and immune checkpoint inhibitors (ICIs) have not been reported, the aim of this study is to investigate the influence of ACE inhibitors on non-small cell lung cancer (NSCLC) patients treated with programmed cell death-1 (PD-1)/programmed cell death-ligand 1 (PD-L1) inhibitors. We conducted a retrospective cohort analysis of NSCLC patients treated with PD-1/PD-L1 inhibitors. Clinical and co-medication data as well as tumor biopsies were collected. Groups were defined according to patients' co-medications at the time of ICI initiation. Among the 178 patients included, 22 (13.1%) received ACE inhibitors. While baseline characteristics were similar in both groups, ACE inhibitors group had a shorter median PFS (Progression-Free Survival) compared to the control group: 1.97 vs. 2.56 months, p = .01 (HR = 1.8 CI95% 1.1–2.8). Using CIBERSORT, RNA sequencing suggested that tumors from the ACE inhibitors group had less M1 macrophages, activated mast cells, NK cells and memory activated T cells, thus suggesting an immunosuppressed state. In vitro, the ACE inhibitor, captopril, induced M2 marker at the cell surface of monocytes engaged into M1 differentiation. Thus, ACE inhibitors prescription concomitant to PD-1/PD-L1 inhibitors treatment seems to be associated with impaired outcome and with a tumor immunosuppressed state in patients with advanced NSCLC. These results should be validated in larger prospective cohorts.